2008
DOI: 10.1182/blood-2007-05-092759
|View full text |Cite
|
Sign up to set email alerts
|

Short telomeres are associated with genetic complexity, high-risk genomic aberrations, and short survival in chronic lymphocytic leukemia

Abstract: Telomere length is associated with mutation status of the immunoglobulin heavy chain variable (IGHV) gene and clinical course in B-cell chronic lymphocytic leukemia (B-CLL). In a B-CLL cohort of 152 patients, we analyzed telomere length, genomic aberrations, IGHV mutation status, CD38 and ZAP-70 expression to study the prognostic impact and associations among these factors. An inverse correlation existed between telomere length and IGHV homology (P < .001), CD38 (P < .001), and ZAP-70 expression (P ‫؍‬ .01). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
125
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 54 publications
16
125
0
5
Order By: Relevance
“…This is apparent from deuterated water incorporation experiments 1 as well as telomere erosion. [2][3][4] We have recently shown that the telomere erosion observed in CLL patients is extensive and can result in the loss of telomere function resulting in telomeretelomere fusion events, some of which were clonal; 5 this work also revealed telomeric loss of heterozygosity as well as largescale genomic rearrangements that were concomitant with telomere dysfunction. Telomere dysfunction may therefore account for clonal evolution and the occurrence of large-scale genomic rearrangements, including the loss of 17p and 11q, that confer a poor prognosis and are associated with short telomeres.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…This is apparent from deuterated water incorporation experiments 1 as well as telomere erosion. [2][3][4] We have recently shown that the telomere erosion observed in CLL patients is extensive and can result in the loss of telomere function resulting in telomeretelomere fusion events, some of which were clonal; 5 this work also revealed telomeric loss of heterozygosity as well as largescale genomic rearrangements that were concomitant with telomere dysfunction. Telomere dysfunction may therefore account for clonal evolution and the occurrence of large-scale genomic rearrangements, including the loss of 17p and 11q, that confer a poor prognosis and are associated with short telomeres.…”
mentioning
confidence: 68%
“…Telomere dysfunction may therefore account for clonal evolution and the occurrence of large-scale genomic rearrangements, including the loss of 17p and 11q, that confer a poor prognosis and are associated with short telomeres. 3 Short telomeres and telomeric DNA damage are also associated with the development of resistance to DNA damage-induced apoptosis. 6 The telomere dynamics described in CLL are indistinguishable from those observed experimentally in fibroblast cells undergoing a telomere driven 'crisis' in culture following the abrogation of the p53 pathway.…”
mentioning
confidence: 99%
“…25,26 Subsequent reports outlined the existence of patients in which discordance exists between TL and IGHV-MS and suggested a superior predictive value of TL. 28,29 Finally, Roos et al 47 were able to link TL with poor cytogenetics in a series of 152 patients, including samples collected both at diagnosis and after treatment. Notably, the independent effect of TL on OS was not demonstrated in any of the previously published reports.…”
Section: Discussionmentioning
confidence: 99%
“…This same validation procedure used for TL is commonly used to corroborate clinically and/or biologically based prognostic indicators and has been used also in the CLL field in a recent analysis comparing the relative value of CD38, ZAP70 and VHMS. [47][48][49] The identification and validation of a robust cutoff point is a prerequisite for widespread application of any biomarker. Previous studies in CLL used the median or the mean value of TL, ranging from 4300 to 6000 bp among series, to perform survival comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years telomere length (TL) has been intensively studied in relation to risk and survival of various cancer types, including hematological ones. 5,26,37,38 In particular in a very recent study performed within the European prospective investigation on cancer (EPIC), Hosnijeh et al 39 have shown that longer telomeres are associated with increased risk of MM. In most epidemiological studies TL is measured in DNA from peripheral blood and used as a proxy for TL in other tissues.…”
mentioning
confidence: 99%